Post-stroke health-related quality of life following lower-extremity constraint-induced movement therapy - An observational survey study - Ingela Marklund; Brynjar Fure; Maria Klässbo; Per Liv; Britt-Marie Stålnacke; Xiaolei Hu (PLoS ONE, 2025)
Lower- extremity constraint-induced movement therapy (LE-CIMT) has proven effective in overcoming physical disabilities. Participating in the LE-CIMT requires some independent walking ability without aids that indicates a higher level of motor function than for the entire stroke population. However, only few studies evaluated health-related quality of life (HRQoL) after LE-CIMT. This study aimed to compare HRQoL of people who had participated in LE-CIMT post-stroke to the general population and evaluate whether descriptive characteristics and clinical result were associated with their HRQoL. An observational survey study with a questionnaire including the Swedish RAND-36 and Saltin–Grimby Physical Activity Level Scale was sent to 162 people. Reference data from the Mid-Health Survey in Sweden was used for norm-based comparisons of RAND-36. Respondents’ result from six-minute walk test post-LE-CIMT were used in the univariate analyse. The response rate was 65% (n = 106; 69 males and 37 females with a mean age of 62 ± 12 years). Ninety percent of the respondents could move around indoors and outdoors independently, despite this, 21% considered themselves physically inactive. The respondents had significantly reduced HRQoL compared to the general population in four of eight domains in the RAND-36: physical functioning (p = 0.001), role-functioning (physical; p < 0.001), general health (p = 0.010), and social functioning (p < 0.001). Regression analysis showed that longer walking distance significantly was associated with the RAND-36 physical functioning domain (β = 6.45, 95% confidence interval = 2.03–10.87, p = 0.005). People in the chronic phase post-stroke who had previously participated in LE- CIMT had reduced HRQoL compared to the general population regarding physical functioning, role-functioning physical, general health, and social functioning. A longer walking distance was associated with higher HRQoL in physical functioning domain, emphasising the importance of mobility training in post-stroke rehabilitation.